Presisi dan Akurasi Modul GY-271 - RAMADHAN, MOCHAMMAD WEGIA; SYAFITRI, NIKEN (e-Proceeding FTI, 2024)
In modern times digital compass sensors are widely used because of their smaller size and can be combined with various kinds of electronic devices. One type of digital compass sensor that is inexpensive and easy to obtain is the GY-271 module. The GY-271 module is one of the sensors that is often used in various projects. However, it is necessary to carry out further tests on the accuracy and precision of the sensor, when it is used as the main sensor in a navigation system. The test is carried out by placing the sensor over a protractor with a scale of 0° to 360°. a value of 0° is calibrated using a smart phone connected to GPS. Then the sensor is shifted from position 0° to 315° with a difference of 45°. The test results carried out by this sensor have an average accuracy value of 19.2° and an average precision of 4.29°. The conclusion from this experiment is that the sensor has poor accuracy and precision values. This sensor is not suitable to be applied to systems requiring high levels of accuracy and precision. Keywords: sensor, compass, IC HMC5883L, characteristics, precision, accurate ABSTRAK Pada masa modern sensor kompas digital banyak digunakan karena ukurannya yang lebih kecil dan dapat dikombinasikan dengan berbagai macam alat elektronik. Salah satu tipe sensor kompas digital yang murah dan mudah didapatkan adalah modul GY-271. Modul GY-271 adalah salah satu sensor yang sering digunakan pada berbagai projek. Namun perlu diadakan pengujian lebih lanjut dalam keakurasian dan kepresisian sensor, bila digunakan sebagai sensor utama pada sistem navigasi.. Pengujiandilakukan dengan meletakan sensor di atas busur derajat dengan skala 0° sampai 360°. nilai 0° dikalibrasikan dengan menggunakan ponsel pintar telah terhubung dengan GPS. Kemudian sensor digeser dari posisi 00 sampai 315° dengan selisih kenaikan 45° Hasil pengujian yang dilakukan sensor ini memiliki nilai rata- rata akurasi 19,2° dan rata- rata presisi 4,29°. Kesimpulan dari percobaan ini sensor memiliki nilai akurasi dan presisi yang kurang baik. Sensor ini tidak cocok diaplikasikan pada sistem membutuhkan tingkat keakurasian dan presisi yang tinggi.